A Case Report on Bilateral Synchronous Breast Cancer in Elderly Man - Unmesh Vidyadhar Takalkar; Shilpa Balaji Asegaonkar; Balaji Narayan Asegaonkar; Pushpa Ravindra Kodlikeri (Research Developments in Medicine and Medical Science Vol. 2, 2023)
We describe a rare case of synchronous bilateral breast cancer in an elderly male without any significant risk factors. Globally, breast cancer in men is exceedingly uncommon. The misinterpretation of signs and symptoms and lack of a proper medical history can lead to the progression of rare conditions to advanced stages. A 75-year- old male was presented with mass in right breast. After thorough clinical evaluation he underwent modified radical mastectomy for excision of tumor. Histopathologically, it was invasive duct carcinoma of grade II, stage II and positive for estrogen and progesterone receptors. Radiotherapy, adjuvant chemotherapy, and oral tamoxifen 20 mg daily were used to treat the patient. Three months later, a new lump in the opposite breast was discovered. Once more, the patient underwent a modified radical mastectomy after being given the diagnosis of stage II and grade II invasive duct carcinoma. He underwent hormone therapy as well as radiotherapy. We managed the case of synchronous bilateral breast cancer successfully at our center. After bilateral modified radical mastectomy patient received radiotherapy, adjuvant chemotherapy and hormonal therapy with tamoxifen. In our case also patient had this common type of breast cancer, but within a period of three months he developed same type of tumor on contra lateral side. We managed the case with bilateral modified radical mastectomy, radiotherapy, adjuvant chemotherapy and hormonal therapy with tamoxifen. The correct clinical assessment, mammography, and fine-needle cytology are crucial in the diagnosis of male breast cancer. To best manage patients with male breast cancer, in-depth research on the etiopathology of the disease is required.